The use of intravitreal anti-vascular endothelial growth factor injection and its complications in Chiang Mai University Hospital. - Kunavisarut P. (2014)
To report the use of intravitreal (IVT) injections of anti-vascular endothelial growth factor agents (anti-VEGF) and its complications. The authors performed a retrospective review of consecutive patients treated with IVT injection of anti-VEGF between May 2006 and December 2010 at Chiang Mai University Hospital. Demographic data and complications were registered. The present study included 1,006 eyes of 878 patients. Mean age was 60 years (range 1 month to 91 years). Mean follow-up time was 12 months (range 1 month to 54 months). Total injections were 2,077 given as 47, 210, 399, 575, and 846 injection per year between 2006 and 2010, respectively. Anti-VEGF agents were bevacizumab (1,878; 90.42%), ranibizumab (190; 9.15%), and pegaptanib (9; 0.43%). Indications for injection based on primary diagnosis were neovascular macular degeneration (38.5%), diabetic retinopathy (38%), and retinal vein occlusion (15.9%). The incidence of endophthalmitis was 0.048% (1/2,077) for all injections and 0.053% (1/1878)for bevacizumab. The use of IVT injections of anti-VEGF is increasing, especially the use of bevacizumab. Incidence of ocular and systemic complications after IVT injection of anti- VEGF was low with no significant difference among the three anti-VEGFs agents.